2004
DOI: 10.1046/j.0022-202x.2004.22216.x
|View full text |Cite
|
Sign up to set email alerts
|

RPE65 of Retinal Pigment Epithelium, A Putative Receptor Molecule for Plasma Retinol-Binding Protein, is Expressed in Human Keratinocytes

Abstract: Retinoids are important modulators for cell growth and differentiation of normal skin. In plasma, retinol is transported coupled to plasma retinol-binding protein. In this study, we investigated gene and protein expression of RPE65, a putative receptor for plasma retinol-binding protein in human epidermal keratinocytes. We performed real-time PCR analysis to evaluate expression of RPE65 mRNA in proliferating and differentiating keratinocytes. Immunoblotting with anti-RPE65 antibody shows distinct reactivity to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
22
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 56 publications
(88 reference statements)
2
22
0
Order By: Relevance
“…Interestingly, we also find rpe65a , well-known to be expressed in RPE, to also be expressed by melanocytes. This is not entirely surprising, as RPE65 is known to be present in keratinocytes, melanocytes, and melanoma, in addition to the RPE [46], [47]. Thus, using this method, cDNA from melanocytes, iridophores, and RPE can be generated concomitantly from thousands of whole zebrafish embryos in a single day.…”
Section: Resultsmentioning
confidence: 97%
“…Interestingly, we also find rpe65a , well-known to be expressed in RPE, to also be expressed by melanocytes. This is not entirely surprising, as RPE65 is known to be present in keratinocytes, melanocytes, and melanoma, in addition to the RPE [46], [47]. Thus, using this method, cDNA from melanocytes, iridophores, and RPE can be generated concomitantly from thousands of whole zebrafish embryos in a single day.…”
Section: Resultsmentioning
confidence: 97%
“…Although RPE65 is highly abundant in the RPE, it is also found in many locations, typically in association with vitamin A metabolism and/or with melanocytes. For instance, RPE65 is also found to be expressed, at mRNA and/or protein levels, in human cones (Tang et al, 2011), bovine ciliary epithelial tissue (Salvador-Silva et al, 2005), mouse hypothalamus (Helfer et al, 2012), and in keratinocytes (Hinterhuber et al, 2004) and melanocytes (Amann et al, 2012) in human skin. In tree shrews, preliminary results comparing differential mRNA expression in RPE with that in choroid have found that mRNA for RPE65 is not differentially regulated after one day of −5 D lens wear, whereas it is significantly up-regulated in the choroid.…”
Section: Discussionmentioning
confidence: 99%
“…Because the microarray was produced from cDNA libraries derived from chick pineal glands, it is important to point out here that retinaspecific sequences (genes expressed in the retina but not the pineal gland), such as rhodopsin, are not represented here. Nonetheless, several genes associated with visual transduction were analyzed including melanopsin (Opn4) (35) and rod ␥-subunit phosphodiesterase 6 (Pde6) (36) as well as opsins and binding proteins associated with visual cycle function, such as peropsin (Rrh) (37), retinal G-protein-coupled receptor opsin (Rgr) (38), and retinal pigmented epithelium 65 (Rpe65) (39). The mRNA for all of these genes was expressed rhythmically under both LD and DD conditions with the exception of melanopsin.…”
Section: Resultsmentioning
confidence: 99%